Identification of Novel Compounds That Bind to the HGF β-Chain In Silico, Verification by Molecular Mechanics and Quantum Mechanics, and Validation of Their HGF Inhibitory Activity In Vitro - Ko Suzuki; Keitaro Inoue; Ryota Namiguchi; Seiya Morita; Suzuho Hayakawa; Mikuri Yokota; Katsuya Sakai; Kunio Matsumoto; Shunsuke Aoki (Molecules)
The development of small-molecule drugs targeting growth factors for cancer therapy remains a significant challenge, with only limited successful cases. We attempted to identify hepatocyte growth factor (HGF) inhibitors as novel anti-cancer small-molecule drugs. To identify compounds that bind to the β-chain of HGF and inhibit signaling through HGF and its receptor Met interaction, we performed a hierarchical in silico drug screen using a three-dimensional compound structure library (Chembridge, 154,118 compounds). We experimentally tested whether 10 compounds selected as candidates for novel anticancer agents exhibit inhibition of HGF activity. Compounds 6 and 7 potently inhibited Met phosphorylation in the human EHEMES-1 cell line, with IC50 values of 20.4 and 11.9 μM, respectively. Molecular dynamics simulations of the Compound 6/7–HGF β-chain complex structures suggest that Compounds 6 and 7 stably bind to the interface pocket of the HGF β-chain. MM-PBSA, MM-GBSA, and FMO analyses identified crucial amino acid residues for inhibition against the HGF β-chain. By interfering with the HGF/Met interaction, these compounds may attenuate downstream signaling pathways involved in cancer cell proliferation and metastasis. Further optimization and comprehensive evaluations are necessary to advance these compounds toward clinical application in cancer therapy.